UPAYA PENINGKATAN CAKUPAN ASI EKSKLUSIF DAN INISIASI MENYUSU DINI (IMD - Santi, Mina Yumei (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2017)
Infant mortality rate by Indonesia Demographic Health Survey in 2012 is still quite high at 32 per 1,000 live births and under five year mortality rates of 40 per 1,000 live births. An effort to prevent infant mortality is by breastfeeding soon after birth or so-called early initiation of breastfeeding and exclusive breastfeeding. Coverage of exclusive breastfeeding nationwide in 2014 amounted to 52.3% is still below the national target of 80%. The aim of this research was to find the efforts to improve the coverage of exclusive breastfeeding and the early initiation of breastfeeding. The Efforts that can do are empowering people through Mother Support Group, socialize the Government Regulation No. 33 of 2012 on exclusive breastfeeding and breastfeeding counselor provides power. The local government is advised to draw up local regulations that support the implementation of the early initiation of breastfeeding program and exclusive breastfeeding so as to have binding legal force for all parties involved as well as to conduct promotion, monitoring, evaluating and supervising the implementation and achievement of the program exclusive breastfeeding.